2019
DOI: 10.3389/fnhum.2019.00285
|View full text |Cite
|
Sign up to set email alerts
|

Speed-Accuracy Tradeoffs in Brain and Behavior: Testing the Independence of P300 and N400 Related Processes in Behavioral Responses to Sentence Categorization

Abstract: Although the N400 was originally discovered in a paradigm designed to elicit a P300 (Kutas and Hillyard, 1980 ), its relationship with the P300 and how both overlapping event-related potentials (ERPs) determine behavioral profiles is still elusive. Here we conducted an ERP ( N = 20) and a multiple-response speed-accuracy tradeoff (SAT) experiment ( N = 16) on distinct participant samples using an antonym paradigm ( The opposite of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 73 publications
(146 reference statements)
0
13
0
Order By: Relevance
“…We found a more positive response for misspelled words than for correctly spelled words only for highfrequency words in the right anterior region. The P300 wave is not a component exclusively related to language processing; however, it is found in any psycholinguistic paradigm that requires an assessment of stimulus and a binary decision (Proverbio et al, 2009;González-Garrido et al, 2014;Alday and Kretzschmar, 2019). This wave reflects an information-processing cascade when attentional and memory mechanisms are engaged, namely, final stimulus evaluation (Polich, 1985(Polich, , 2004Taylor, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found a more positive response for misspelled words than for correctly spelled words only for highfrequency words in the right anterior region. The P300 wave is not a component exclusively related to language processing; however, it is found in any psycholinguistic paradigm that requires an assessment of stimulus and a binary decision (Proverbio et al, 2009;González-Garrido et al, 2014;Alday and Kretzschmar, 2019). This wave reflects an information-processing cascade when attentional and memory mechanisms are engaged, namely, final stimulus evaluation (Polich, 1985(Polich, , 2004Taylor, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The ERP results in this experiment showed that word frequency influences the error recognition process in later stages. The N400 component found in lexical or semantic categorization tasks is overlapped by the modulation of P300, a component associated with attention mechanisms activated to perform a task (Polich, 1985, 2004; van Hees et al, 2017; Alday and Kretzschmar, 2019; Bermúdez-Margaretto et al, 2019). In our study, we also observed a positive wave in the frontal regions, along with a negative wave in the central parietal areas.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, prediction match is achieved, as visible in an increase in P300 amplitude as compared to the less prominent referents with noun antecedent. Following Alday and Kretzschmar (2019) , if we wanted to provide a cognitive explanation for the P300 effect, we might say that the P300 reflects the immediate categorization of pronoun anaphors with pronoun antecedents, in the sense that they can be directly linked to a referent in the discourse model without the need for further evidence (e.g., by subsequent context). In other words, as mentioned in the introduction, we argue that pronominal reference to prominent referents is predicted to the extent that the referential relation is anticipated before the anaphoric pronoun is actually detected.…”
Section: Discussionmentioning
confidence: 99%
“…If, as it was the case in the related and unrelated condition, there occurs prediction error with regard to linguistic meaning, the same biphasic N400-P600 pattern as in Schumacher et al (2015) can be observed. As discussed in Alday and Kretzschmar (2019) , the N400 and P300 both seem to be sensitive to prediction, yet while the N400 reflects the processing of stimulus related features (e.g., linguistic prominence features) necessary for categorization, the P300 reflects the categorization process itself. Accordingly, in the absence of prediction error, no further information is needed for stimulus classification, hence the early P300 in Roehm et al (2007) , while with linguistic prediction error, and hence, categorization uncertainty, an N400 arises, reflecting the processing of stimulus features relevant for categorization (“evidence accumulation”).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation